A Comparative Analysis on the Status of Laboratory Resources And Science Process Skills of Grade 11 Learners in The Schools Division of Eastern Samar, Philippines - Noroña, Roselle V. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Instructional resources play a significant role in the development of man’s scientific thinking. Thus, a hybridized descriptive correlational inquiry was conducted to examine the present availability and utilization statuses of science laboratory resources and the mastery level on integrated science process skills among 274 Grade 11 learners in three secondary schools in the schools’ division of Eastern Samar using a researcher-developed questionnaire on the availability and utilization status of basic science laboratory resources, and an adopted integrated science process skills test of Monica (2005) for the school year 2019-2020. Findings revealed a significant difference in terms of availability, utilization, and mastery levels among the three participating secondary schools in the schools division of Eastern Samar. Hence, it is recommended for the education sector to propose and develop a laboratory resource management system so that the availability and utilization of science instruments will be maximized, and an intervention program be provided among students to heighten their present integrated science process skills mastery level.